Immune responses in sheep naturally infected with Oestrus ovis (Diptera: Oestridae) and gastrointestinal nematodes - Silva, B. F. [UNESP]; Bassetto, C. C. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B.V., 2012)
This study was carried out to evaluate the immune response in young Ile de France (IF) and Santa Ines (SI) sheep naturally infected by Oestrus ovis and gastrointestinal nematodes (GIN). Mast cells, eosinophils and globule leucocytes were enumerated in the upper respiratory tract (septum, middle meatus and ventral nasal conchae) and in the mucosa of abomasum and small intestine. Immunoglobulin G (IgG) levels in serum samples and immunoglobulin A (IgA) levels in mucus from the nasal, abomasum and small intestinal mucosae were determined against O. ovis, Haemonchus contortus and Trichostrongylus colubriformis antigens. Significant positive correlation coefficients were observed in both breeds between the number of O. ovis larvae x IgG against Oestrus crude extract (IF: r = 0.58; SI: r = 0.66; P < 0.05), and between O. ovis larvae x IgG against Oestrus excretory and secretory products (IF: r = 0.59; SI: r = 0.63; P < 0.05). Apparently, the presence of antibodies in the serum or nasal mucus, as well as inflammatory cells, was not able to efficiently protect against O. ovis infestation. With regard to GIN, the levels of immunoglobulins and the inflammatory cell numbers in the gastrointestinal mucosa presented a significant inverse relationship with H. contortus worm burden in SI animals and this may have contributed to the fact that these animals presented the lowest FEC and worm burden compared to IF. In conclusion, the immune responses against O. ovis and GIN are very similar and involve the recruitment of inflammatory cells and production of immunoglobulins against the parasites. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Immune response; Sheep; Oestrus ovis; Haemonchus contortus; Trichostrongylus colubriformis